1993
DOI: 10.1017/s0025315400032859
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophy in marine species of Chrysochromulina (Prymnesiophyceae): ingestion and digestion of a small green flagellate

Abstract: Species of Chrysochromulina (Prymnesiophyceae) were screened for their ability to ingest inert material and live cells of a small green flagellate. The species C. brevifilum showed a marked preference for the small green flagellate over carmine particles and the rate of ingestion of the flagellate was proportional to its concentration and inversely proportional to light intensity. Ingestion was also higher by phosphate-starved Chrysochromulina, and a clear predator/prey relationship was demonstrated with C. br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 32 publications
4
83
0
1
Order By: Relevance
“…Evidence for dissolved iron use by mixotrophic phytoplankton-The three flagellates examined in this study were mixotrophic phototrophs that had been shown to ingest bacteria (Jones et al 1993;Maranger et al 1998) and to use them as their sole iron source in growth (Figs. 7, 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for dissolved iron use by mixotrophic phytoplankton-The three flagellates examined in this study were mixotrophic phototrophs that had been shown to ingest bacteria (Jones et al 1993;Maranger et al 1998) and to use them as their sole iron source in growth (Figs. 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…The flagellates, Ochromonas sp., Chrysochromulina cf ericina, and C. ericina were mixotrophic species, capable of ingesting bacteria and other particles (Jones et al 1993;Maranger et al 1998). T. pseudonana was maintained in axenic culture, but cultures of the other isolates contained low densities of bacteria (ϳ10 4 -10 5 ml Ϫ1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This point should be kept in mind when interpreting earlier studies of food uptake in mixotrophs (e.g. Jones et al 1993, Hansen & Nielsen 1997, Skovgaard 1998, Jeong et al 1999, Li et al 1999. Ingested carbon and photosynthate probably differ in the efficiency and pathways by which they are metabolized by a mixotroph and may have different fates within a cell.…”
Section: Gross Carbon Budgetmentioning
confidence: 99%
“…the relative importance of feeding for survival and growth, and the influence thereon of biotic and abiotic factors. Light has been shown to have different effects on feeding activity in different species, varying from stimulation (Caron et al 1993) to inhibition of feeding (Jones et al 1993), but the effect of light on feeding can also be more complex (Skovgaard 1996a), or in some cases negligible (Andersson et al 1989, Jeong et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…So far it has only been referred to as a 'small green flagellate' (Jones et al, 1993) and it is described here as the type representative of a new genus.…”
Section: Introductionmentioning
confidence: 99%